A facile route for constructing Cu–N–C peroxidase mimics. Issue 37 (21st August 2020) - Lin, Zhen; Zheng, Linlin; Yao, Wensong; Liu, Shijun; Bu, Yemei; Zeng, Qi; Zhang, Xiaomin; Deng, Haohua; Lin, Xinhua; Chen, Wei
Abstract : Cu–N–C single-atom nanozymes were successfully designed via a one-pot solvothermal method and their excellent peroxidase-mimicking activity has been investigated and applied for H2 O2 and glucose determination. Abstract : Nanozymes have emerged as enzyme-mimicking nanomaterials to overcome the low stability and high cost of some natural enzymes. The design and fabrication of nanozymes with superior performance to natural enzymes are in urgent demand. Single-atom catalysts offer the unique characteristics of maximum atomic utilization, and are an excellent candidate for nanozymes. However, most of the reported synthesis methods for single-atom catalysts require the preparation of supports for single-atom catalysts in advance, which requires multiple steps and calcination in a high temperature atmosphere. Herein, Cu–N–C single-atom nanozymes (Cu–N–C SAzymes) were successfully designed via a one-pot solvothermal method. Cu–N–C SAzymes exhibited excellent peroxidase-mimicking activity that is superior to some other related nanoparticles. The mechanism study revealed that H2 O2 was catalyzed by Cu–N–C SAzymes to generate reactive oxygen species. Furthermore, based on the excellent peroxidase-mimicking activity of the Cu–N–C SAzymes, a simple and sensitive detection method for H2 O2 and glucose has been developed.